Re-Layout of Puskesmas X Post-Covid 19 Pandemic Through the ARC, Conventional and Promodel Simulation Methods - Bhagya, Tombak Gapura; Yulianti, Dini; Prakarsa, Graha; Gitardiana, Antari Nurayban (Sainteks: Jurnal Sain dan Teknik, 2023)
The Community Health Center (Puskemas) is the foremost and closest place to provide health services to the community. With the BPJS and complete facilities, the Puskesmas is now almost the favorite of the people to get health-related consultation and treatment. So this study tries to make an analysis of puskesmas services and evaluate the layout and queues in the puskesmas using Promodel simulations. The simulation is used because of the fluctuating number of patients who come every day, so that with the simulation the process of estimating patient arrivals can be carried out using statistical distribution estimates. The results of this study indicate the need for a new layout change, where with this new layout the patient's time in the system can be reduced and the need for adding doctors to 2 to 3 people to cut the number of queues that have accumulated waiting to be examined by a doctor. If the point of adding doctors cannot be met, then the puskesmas can provide adequate waiting room facilities for patients who will be examined by a doctor. The ideal number of waiting room seats for patients waiting to be examined by a doctor is 38 seats.